MicroRNA-19b-3p suppresses gastric cancer development by negatively regulating neuropilin-1 - Yingfeng Wei; Sheng Guo; Jianhua Tang; Jianjun Wen; Huifen Wang; Xiaobo Hu; Qiuping Gu (Cancer Cell International, 2020)
Abstract Background Gastric cancer (GC) remains one of the most common digestive malignancies worldwide and ranked third causes of cancer-related death. Mounting evidence has revealed that miRNAs exert critical regulatory roles in GC development. Methods Immunohistochemistry (IHC) and western blot assay were performed to determine the protein expression levels of neuropilin-1 (NRP1) and mRNA levels were confirmed by quantitative RT-PCR (qRT-PCR) in GC tissues. Kaplan–Meier analysis was performed to evaluate the prognostic value of NRP1 in GC. Knockdown of NRP1 was conducted to analyse its function in vitro and vivo. Luciferase reporter assay, western blot and qRT-qPCR were employed to identify the miRNAs which directly targeted NRP1. Furthermore, Bioinformatics analysis and experimental verification were used to explore the potential molecular mechanism and signalling pathway. Results In the current study, we revealed that NRP1 was highly expressed in GC tumor tissues and was associated with poor prognosis in GC patients. NRP1 knockdown inhibited GC cell growth, migration and invasion in vitro, while suppressed GC xenograft tumor development in vivo. Bioinformatics analysis predicted that miR-19b-3p down-regulated NRP1 expression by targeting its 3′-UTR. Functional assay demonstrated that miR-19b-3p inhibited GC cell growth, migration and invasion via negatively regulating NRP1. Overexpression NRP1 partially reversed the regulatory effect of miR-19b-3p. Moreover, we showed that miR-19b-3p/NRP1 axis regulated the epithelial-to-mesenchymal transition and focal adhesion in GC, which might contribute the GC development and progression. Conclusions Taken together, our findings suggest a regulatory network of miR-19b-3p/NRP1 in GC development. The miR-19b-3p/NRP1 axis might be further explored as a potential diagnostic and therapeutic target in GC.